Use of psychiatric medication in three Arctic nursing homes: association with dementia and psychiatric symptoms. Issue 1 (1st January 2021) - Gisladottir, Sigurveig; Sigurdardottir, Arun K.; Hjaltadottir, Ingibjörg
ABSTRACT: As more people reaches advanced age, more people experience cognitive impairment and dementia. Dementia is a degenerative disease in which behavioural and psychological symptoms frequently occur, resulting in admissions to nursing homes (NHs), where the most common treatment has been medical treatment. The aim was to compare three rural Arctic NHs in Iceland in their use of psychiatric medication, type of dementia among residents, level of cognitive impairment and selected quality indicators, as well as considering national data, for the period 2016–2018. Data from the interRAI-MDS 2.0 evaluation were used. Residents with severe cognitive impairment used more antipsychotic medications, and residents with mild and severe cognitive impairment used more antidepressants than residents with no cognitive impairment did. Diagnoses of Alzheimer's Disease and Related Dementias (ADRD) are more common in the capital area and the national average than they are in the rural NHs. This indicates need for diagnostic assessments of ADRD to be conducted in rural areas. Benchmarking is beneficial for local and national regulatory bodies to find areas for improvement. The NHs did not have a lower quality of care compared with the whole country, but areas for improvement were identified. One of the NHs has already started this process.